WHAT CONVINCED THE WORLD COMMUNION OF REFORMED CHURCHES IN 1998 AND WORLD COUNCIL OF CHURCHES IN 2015 TO READMIT THE DUTCH REFORMED CHURCH AS A FULL MEMBER? - Strauss, P (Acta Theologica, 2018)
As members of the World Council of Churches, the two synods of the Dutch Reformed Church broke their ties with this institution in 1961, following the critisism of the Cottesloe Consultation of 1960 on apartheid. The World Alliance of Reformed Churches, which became part of the World Communion of Reformed Churches in 2010, declared a status confessionis against the theological and moral justification of apartheid and suspended the membership of the Dutch Reformed Church at Ottawa in 1982. As a result of the changes effected in South Africa and the Dutch Reformed Church, the latter was readmitted as full member of the Alliance in 1998. In 2007 the Dutch Reformed Church applied for membership of the World Council. It was granted in 2015.